Modifications of Protein Environment of the [2Fe-2S] Cluster of the bc(1) Complex: EFFECTS ON THE BIOPHYSICAL PROPERTIES OF THE RIESKE IRON-SULFUR PROTEIN AND ON THE KINETICS OF THE COMPLEX - Lhee, Sangmoon (American Society for Biochemistry and Molecular Biology, 2010)
The rate-determining step in the overall turnover of the bc(1) complex is electron transfer from ubiquinol to the Rieske iron-sulfur protein (ISP) at the Q(o)-site. Structures of the ISP from Rhodobacter sphaeroides show that serine 154 and tyrosine 156 form H-bonds to S-1 of the [2Fe-2S] cluster and to the sulfur atom of the cysteine liganding Fe-1 of the cluster, respectively. These are responsible in part for the high potential (E(m)(,7) ∼300 mV) and low pK(a) (7.6) of the ISP, which determine the overall reaction rate of the bc(1) complex. We have made site-directed mutations at these residues, measured thermodynamic properties using protein film voltammetry to evaluate the E(m) and pK(a) values of ISPs, explored the local proton environment through two-dimensional electron spin echo envelope modulation, and characterized function in strains S154T, S154C, S154A, Y156F, and Y156W. Alterations in reaction rate were investigated under conditions in which concentration of one substrate (ubiquinol or ISP(ox)) was saturating and the other was varied, allowing calculation of kinetic terms and relative affinities. These studies confirm that H-bonds to the cluster or its ligands are important determinants of the electrochemical characteristics of the ISP, likely through electron affinity of the interacting atom and the geometry of the H-bonding neighborhood. The calculated parameters were used in a detailed Marcus-Brønsted analysis of the dependence of rate on driving force and pH. The proton-first-then-electron model proposed accounts naturally for the effects of mutation on the overall reaction.